A Comprehensive Analysis of Cinnamon, Flaxseed, and Lemon Seed Essential Oils’ Effects on In Vitro Gas Formation and Nutrient Degradability in Diets - Maghsoud Besharati; Valiollah Palangi; Masoumeh Niazifar; Selim Esen; Maximilian Lackner (Fermentation, 2023)
This study aimed to assess the impact of essential oils (EOs) on in vitro gas formation and the degradability of dairy and beef cattle diets. This study also aimed to investigate the effects of different types of EOs on nutrient utilization and rumen microbial activity. The current study was conducted using a fully randomized design consisting of eight experimental treatments, including two control treatments without any additives, and treatments with cinnamon essential oil (CEO), flaxseed essential oil (FEO), and lemon seed essential oil (LEO) at a concentration of 60 mg/kg fresh mass. Two control treatments were used, one with alfalfa silage and dairy concentrate (DC, CON-DC) and the other with alfalfa silage and fattening concentrate (FC, CON-FC). Gas formation, dry matter (DM) digestibility, crude protein (CP) digestibility, effective degradability (ED), and soluble fractions of DM and organic matter (OM) were evaluated. CEO had a substantial effect on gas formation (p < 0.05). When EOs were added to the diets, they increased dry matter digestibility after 24 h of incubation as compared to control treatments. After 24 h of incubation, FCCEO and FCFEO had the highest CP digestibility among the diets. FCLEO considerably enhanced ED, as well as the soluble fraction of DM (a) at a passage rate of 2% per hour. Treatment with FCCEO resulted in a significant increase in soluble fractions compared to the control diets. At a passage rate of 2% h, DCCEO had the maximum ED value. When EOs were introduced to the diet, they dramatically decreased the insoluble portion of CP (b). Compared to the control treatments, gas production was significantly lower in the presence of LEO (FCLEO; p < 0.05). The addition of EOs to cattle diets may increase nutrient utilization and enhance rumen microbial activity. EOs extracted from lemon seeds (at a dose of 60 mg/kg of diet) lowered gas production in both dairy cattle and fattening diets.